Mathematical Modeling of Wellbore Flow Behavior in Multilateral Wells - Farah Amalina Azianti Bt Azmi, Farah Amalina Azianti (Universiti Teknologi Petronas, 2012)
In oil and gas industry, the there is no other way to extract the oil but to drill holes through the earth crust. Since 2550 - 2315 BC, the technology of drilling has been evolved with new techniques and materials parallel to the increasing number of ideas and human population. After the oil become core energy sources for mankind, the world focusing on extracting them even more. In search of newest innovations which could make development projects in mature fields more attractive, multilateral well drilling was identified as the most promising emerging technology. Over the past 20 years, with the rapid evolution of the first horizontal wells and eventually multilateral wells, reservoir-to-well exposure has increased dramatically to orders of magnitude larger than before. Then multilateral wells accomplish both of these tasks, the accessing and the exposure effectively. The multilateral well’s exposure is very clear. Also it is expensive to drill other well and thus more laterals within a mother wellbore will give more exposure to the reservoir. The main objective of this project is to develop the computer codes to model the flow behavior in the lateral of multilateral well. Modeling techniques that applied is analytical and numerical approach which implements mathematical software to model the flow behavior in the lateral of multilateral well and perform comparison analysis against different modeling method. The first analysis will consist of the horizontal part of the lateral using no inflow model, Ouyang et al. and Yuan et al. (1998). The analysis will comprise of the model pattern and the effectiveness of each model. The second analysis is done for the build-up section for dual-lateral well. The model used is Beggs and Brill correlation and analysis will be done on two flow conditions which are single phase and multiphase flow. Hypothetical reservoir and well data from research papers and SPE monographs is used to generate the typical well condition for these models. The significance of this study is because the well monitoring especially the flow behavior and pressure drop is one of the key factors in determining the well deliverability and performance. Estimates of well performance assists petroleum engineers to decide the optimum production and reservoir management plan.